Evaluation of Thrombolytic Activity of Four Bangladeshi Medicinal Plants, as a Possible Renewable Source for Thrombolytic Compounds - Sikder, Md. Al Amin; Siddique, Abu Bakar; Hossian, A.K.M. Nawshad; Miah, Md. Kowser; Kaisar, Mohammad A.; Rashid, Mohammad A. (Journal of Pharmacy and Nutrition Sciences, 2022)
Four Bangladeshi medicinal plants Sansevieria trifasciata, Justica gendarussa, Hydnocarpus kurzii and Mesua nagassarium have been investigated for their in vitro thrombolytic activity. The clot lysis activity was assessed by addition of the test material to the pre-clotted blood and incubation for 90 min. at 37oC and was expressed as % lysis of clot. Each of the plant was extracted with methanol at room temperature and the concentrated methanolic extract was fractionated by the modified Kupchan partitioning method to provide pet-ether, carbon tetrachloride, chloroform and aqueous soluble fractions. Among the four plants the aqueous soluble fraction of M. nagassarium, carbon tetrachloride soluble fraction of H. Kurzii , aqueous soluble fraction of methanolic extract of S. trifasciata exhibited highest thrombolytic activity with clot lysis value of 50.86%, 47.50%, and 47.10% respectively. However, the pet ether and carbon tetrachloride soluble fraction of methanolic extract of J. gendarussa demonstrated significant thrombolytic activity as evident from 45.93% and 45.47% lysis of clot, respectively. Standard streptokinase was used as positive control which exhibited 61.50% lysis of clot while the negative control water revealed 2.56% lysis of clot.